A Comparative Analysis of Income Accounting Information System at PT. Hanan Properti Bengkulu - Ida Anggriani; Rinto Noviantoro; Renny Efryanty (Kusuma Negara Business School, 2020)
: The purpose of this study was to determine the comparison of income accounting information system at PT. Hanan Properti Bengkulu. Data collection methods used were documentation and interviews. Documentation was done by collecting the data from sources of existing documents by making copies or relying on existing company records and records regarding the income accounting information system. The interview was done directly to the leadership or employees directly related to the activities of the income accounting information system. The analytical method used was a comparative method of comparing data obtained by the company with the theory presented by Mulyadi. General accounting information system that applies in general, according to Mulyadi, consists of revenue cycles (sales, delivery, billing and cash receipts), related functions (sales function, credit function, recapitulation function, submission function, billing function, accounting function), accounting records used (sales journal, accounts receivable cards, additional cards for receipt of advances, recapitulation and general journals) and document flowcharts (sales section, credit section, recapitulation section, submission section, billing section, accounts receivable section, additional cash receipt card section advance, and journal section). The results of this study indicate that in the comparison of income accounting information system at PT. Hanan Properti Bengkulu, including: income cycle (sales and credit), related functions (internal parties, namely sales and accounting functions, external parties, ie credit functions), records used (realization report, sales recapitulation, sales journal, receipt of money payments advance, additional books for advance payments) and document flow charts (sales department and credit department). So, the comparison of existing accounting information system at PT. Hanan Properti Bengkulu, there is a conformity in the income cycle with the theory, while the accounting records used and the related functions and document flow chart do not correspond to the theory.